An appraisal of the current status of inhibition of glucose transporters as an emerging antineoplastic approach: Promising potential of new pan-GLUT inhibitors - Temre, Mithlesh Kumar; Kumar, Ajay; Singh, Sukh Mahendra (Frontiers in Pharmacology, 2022)
Neoplastic cells displayed altered metabolism with accelerated glycolysis. Therefore, these cells need a mammoth supply of glucose for which they display an upregulated expression of various glucose transporters (GLUT). Thus, novel antineoplastic strategies focus on inhibiting GLUT to intersect the glycolytic lifeline of cancer cells. This review focuses on the current status of various GLUT inhibition scenarios. The GLUT inhibitors belong to both natural and synthetic small inhibitory molecules category. As neoplastic cells express multiple GLUT isoforms, it is necessary to use pan-GLUT inhibitors. Nevertheless, it is also necessary that such pan-GLUT inhibitors exert their action at a low concentration so that normal healthy cells are left unharmed and minimal injury is caused to the other vital organs and systems of the body. Moreover, approaches are also emerging from combining GLUT inhibitors with other chemotherapeutic agents to potentiate the antineoplastic action. A new pan-GLUT inhibitor named glutor, a piperazine-one derivative has shown a potent antineoplastic action, owing to its inhibitory action exerted at nanomolar concentrations. The review discusses the merits and limitations of the existing GLUT inhibitory approach with possible future outcomes.